Anti-PD1-induced collagenous colitis in a melanoma patient. Issue 3 (June 2016) - Baroudjian, Barouyr; Lourenco, Nelson; Pagès, Cécile; Chami, Ichrak; Maillet, Marianne; Bertheau, Philippe; Bagot, Martine; Gornet, Jean-Marc; Lebbé, Céleste; Allez, Matthieu
Abstract : Targeted immunotherapy has markedly improved the survival of melanoma patients. We report the case of a melanoma patient who developed a collagenous colitis under an anti-PD1 regimen. A 68-year-old woman was treated for a stage IV melanoma. An anti-PD1, pembrolizumab, was introduced after the failure of a first-line therapy with an anti-CTLA4. At cycle 14, pembrolizumab was interrupted because of grade 3 diarrhea. Histologic analysis of colon mucosa showed a thickened apical subepithelial collagen layer with irregular collagen deposition of more than 25 µm thickness. Budesonide 9 mg/day and cholestyramin 8 g/day were then introduced, leading to a decrease in the number of stools to grade 2. Because of the prognosis of the disease, the efficacy of pembrolizumab in this patient and the lack of other efficient treatments, pembrolizumab was restarted, with no worsening of the diarrhea after a follow-up of 8 weeks. In the era of immunotherapy, a new type of drug-induced colitis has emerged because of monoclonal antibodies targeting immune checkpoints such as CTLA-4 and PD1. Gastrointestinal tract immune-mediated adverse effects are now well described with ipilimumab. To the best of our knowledge, this is the first report of a collagenous colitis in a patient treated with pembrolizumab, thus suggesting a new mechanism of toxicity. Classically, collagenous colitis first-line treatment is based on discontinuation of the suspected treatment. However, there may be a strong benefit to maintaining an anti-PD1 regimen in our patients. In this case, symptomatic management associated with budesonide and cholestyramin enabled continuation of pembrolizumab.